Minimizing the energy consumption of WSN by using modified hybrid energy efficient distributed clustering protocol - K Thomas, Aby; R, Vallikannu; Advait Narayanan, Sai (International Journal of Engineering and Technology, 2018)
Wireless Sensor Networks use batteries for supplying power to the sensor nodes. Batteries are capable of supplying only a limited amount of power. Wireless Sensor Networks are making use of node clustering with the aim of reducing the network power requirements thereby increasing the network lifetime. Various clustering algorithms are being made use of today for the purpose of achieving high energy efficiency. Out of all such protocols the Hybrid Energy-Efficient and Distributed Clustering protocol (HEED) is the most energy-efficient clustering algorithm. In the (HEED) protocol the Cluster Head is selected on the basis of the cost of the route within the cluster as well as the residual energy of the node to be selected. The modified HEED protocol has been proposed in this paper. The network is set up by making use of certain procedures that are similar to those used by the HEED protocol. The network periodically refreshes and updates itself in instances known as rounds. At the start of each network round, the Cluster Heads of all the clusters wait for a certain period of time that is defined by the network to obtain a New Cluster Formation notification from the WSN sink.Â defined period of time for receiving a re-clustering message from the sink. If such a notification is not received, the same cluster will continue to scan the other nodes within it in order to select a New Cluster Head that is suited to the present network conditions. The performance simulation shows that the proposed protocol outperforms the original protocol with regards to the lifetime of the network. In this paper, the Custer Head is selected by searching the nodes by giving importance to the residual node energy instead of searching the nodes in a random manner. NS2 Software is used to simulate the network performance. The results clearly indicate that the performance of the network has improved in terms of energy efficiency, Quality Of Service and other performance parameters.Â Â